The Teacher’s Perception of Reinforcement and Its Impact on Student Engagement in English Language Learning: A Qualitative Study - Ramadhani, Ananda Salsabilah; Abduh, Amirullah; Halim, Abdul (Fakultas Sastra - Universitas Muslim Indonesia, 2025)
This study explores the perception of an English teacher regarding the use of reinforcement and its impact on student engagement in English language learning. Conducted at SMPN 40 Makassar, the research utilized a qualitative descriptive approach to investigate how the teacher views reinforcement as a tool to support behavioral, emotional, and cognitive engagement. The primary data were gathered through an in-depth interview with one male eighth-grade English teacher and supplemented by six classroom observations conducted over a three-week period. The findings revealed that the teacher perceives reinforcement not merely as a classroom management technique but as a powerful pedagogical strategy to stimulate motivation, reduce learning anxiety, and foster students’ sense of belonging and competence in the English classroom. Verbal reinforcement, such as praise and addressing students by name, and non-verbal reinforcement, such as smiling, gestures, and eye contact, were consistently applied throughout the observed lessons. The teacher also emphasized the importance of applying reinforcement equitably and intentionally, tailoring it to the diverse personalities and needs of students. These insights align with the theoretical frameworks of Skinner, Bandura, Deci & Ryan, and Fredricks et al. Reinforcement, as perceived and practiced by the teacher, plays a significant role in enhancing student engagement and creating an inclusive, supportive learning environment.